A Bibliometric analaysis: Public Health Services in Singapore and Thailand - Jihan Fadhilah Alrizal; Achmad Nurmandi; Aulia Nur Kasiwi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
The aim of this study is to ascertain the extent to which public services in the health sector are provided in Singapore and Thailand. Research methods include qualitative research techniques in conjunction with a literature review methodology. This study uses data collection techniques with research objects derived from papers published from 2017-2022 in the Scopus database. The hospital service system in the two countries has differences, namely, Singapore only has hospitals managed by the government with good and fast services, while in Thailand there are two hospital service systems, namely those managed by hospitals managed by foreigners and hospitals managed by foreigners. by the government. These two countries have made health sector services as health tourism. The public sector is reinventing its business model in response to the need to improve service delivery efficiency. The application of digital technology in the delivery of public services can assist in the paradigm transition from reactive to citizen demands to be proactive